Wood for Domestic Fuel - a 'Crisis' - Chitwadgi, S. S. (Indian Forester)
Firewood scarcity has not provoked much attention. The villagers collect the fuelwood from the forest as a matter of their traditional right. To solve the problem some measures have been suggested which will also help in conserving the environment and reduce pollution.